Male Tolerance to Same-Sex Infidelity: A Cross-Cultural Investigation. (11th April 2019) - Wang, Yan; Apostolou, Menelaos
There is accumulating evidence that heterosexual men exhibit tolerance to their partners' same-sex infidelity. The current study examined such tolerance in the Chinese ( N = 949) and the British ( N = 305) cultural contexts. Consistent with the predictions derived from an evolutionary framework, across different cultural settings, men exhibited higher tolerance than women to their partners' same-sex infidelity. In addition, if they had to choose, men were considerably more likely than women to prefer their partners to cheat with an individual of the same than of the opposite sex. Participants were also more tolerant of infidelity involving their short-term than their long-term partners. Moreover, men who preferred same-sex attraction in women were more tolerant to the same-sex infidelity of their female partners than men who did not share these preferences. Finally, men and women who experienced same-sex attractions indicated higher tolerance to infidelity. The implications of these finding for the evolution of same-sex attraction in women were further discussed.